Devotion in the Bhāgavata Purāna and Christian Love: Bhakti, Agape, Eros - Sheridan, Daniel P. (Horizons, 1981)
The Bhāgavata Purāna, a ninth century encyclopedic Hindu text, combines Vedantic non-dualism and Vaiṣṇava devotionalism or love of God. Its non-dualism accommodates the reality of the universe with its individual selves in the all-encompassing reality of God. The BhP has two forms of devotion: one is a meditation which absorbs the devotee within the unity of God's reality; the other is an ecstasy which glories in separation from God in order to love God more. The Eros-Agape motif is used to compare this tradition of the love of God with those of Christianity, Islam, and Buddhism. Like them, the BhP stresses the personhood of God; unlike them, it stresses an ontological, not a mystical or spiritual, union of Deity and devotee.